Organizational citizenship behavior: Its nature and antecedents - Jahangir, Nadim; Akbar, Mohammad Muzahid; Haq, Mahmudul (BRAC University, 2010)
Theory and research on Organizational Citizenship Behaviors (OCB) has presumed OCB as a set of desirable behaviors that contributes to the organizational effectiveness. So far OCB has been connoted as one of the antecedents of organizational performance. However, the antecedents of OCB are not thoroughly investigated. This study explores various existing definitions of OCB and then examines the dimensions of OCB. Based on the discussion on the dimensions of OCB, a number of antecedents were identified. When the antecedents are known, managers would be able to promote OCB among their employees for better performance.